2022
DOI: 10.1556/606.2022.00582
|View full text |Cite
|
Sign up to set email alerts
|

Application of enhanced coulomb models and virtual tribology in a practical study

Abstract: For the final quality of the part, metal forming trends are depending on improvements of friction and tribology. As a consequence, there is a trend in which tribology and friction are becoming increasingly important for correctly replicating the forming simulation of those parts. The objective of this work was to improve the forming simulation of an automotive shell part on AutoForm. The part was provided by a vehicle industry supplier. Enhanced Coulomb models consider a change on friction coefficient due to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was found that the restraining force normalised by the drawbead width increased with increasing values in the bead height-to-radius ratio. De Carvalho and Lukács [24] used friction shear stress values to detect those places on the workpiece that were exposed to tangential stress caused by contact with the tools and to verify the drawbeads. For the analysed region, the coulomb model was found to be more relevant than the pressure-dependent model for describing friction phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the restraining force normalised by the drawbead width increased with increasing values in the bead height-to-radius ratio. De Carvalho and Lukács [24] used friction shear stress values to detect those places on the workpiece that were exposed to tangential stress caused by contact with the tools and to verify the drawbeads. For the analysed region, the coulomb model was found to be more relevant than the pressure-dependent model for describing friction phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The stamped portion is typically overbent to counteract this effect. One of the most crucial elements affecting contacting surface characteristics of the tool and sheet is the Blank Holding Force (BHF) [3]. Shape variation after sheet forming is mostly influenced by contact surface pressure and friction, and tool geometries [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%